The Vertical and Patronage: Change of the Law Enforcement Elites in Russia’s Regions - R. F. Turovsk; M. S. Sukhova; K. V. Funk (Сравнительная политика, 2024)
The article analyzes the recruitment of the heads of law enforcement agencies in Russian regions. The authors collected extensive biographical dataset on all the heads of the prosecutor’s office and the Ministry of Interior in Russian regions in the post-Soviet period, which made it possible to identify the main patterns for the appointments, transfers among the regions and taking positions in the executive and legislative power bodies and the business after their retirement. The research shows that regional law enforcement agencies are characterized by strictly centralized recruitment that minimizes the ties between the heads of law enforcement services in the regions and local elites. At the same time, few regions with strong local elites and privileged relations with the federal center are able to promote their own representatives to top positions. The study also reveals the formation of clienteles associated with natives of certain areas, whose representatives occupy positions in a large number of federal subjects, as well as in the central office. The research shows that the strengthening of centralization in the law enforcement agencies in Russia is interconnected with the creation of such federal-local clienteles with regional roots and their change when federal heads of law enforcement agencies are replaced which the authors interpret as patronage.